DAMPAK REAL EARNINGS MANAGEMENT TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI MODERATING VARIABLE PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2015–2019 - Nur Indah Aggianti; Nova Novita (Ibs Press, 2024)
The research has a purpose to determine and analyze the impact of real earnings management (REM) on firm value and institutional ownership in moderating the impact of real earnings management (REM) on firm value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2019. The population in this research are a manufacturing companies in food and beverage sub-sector, that obtain sample of 9 companies after through the sample selection process using the purposive sampling method. The result of this research indicate that real earnings management (REM) proxied by abnormal CFO, abnormal production cost, and abnormal discretionary expenses has a negative effect on firm value, institutional ownership is able to moderate the effect of real earnings management (REM) proxied by abnormal CFO, abnormal production costs, and abnormal discretionary expenses on firm value. The implication of the result of this reseach are that company management, the investor, and the academics expected to consider the practice of real earnings management (REM) in order to degrade the firm value.